Versatile method for the preparation of conjugates of peptides with DNA/PNA/analog by employing chemo-selective click reaction in water - Gogoi, Khirud; Mane, Meenakshi V.; Kunte, Sunita S.; Kumar, Vaijayanti A. (Nucleic Acids Research, 2007)
The specific 1,3 dipolar Hisgen cycloaddition reaction known as `click-reaction' between azide and alkyne groups is employed for the synthesis of peptideoligonucleotide conjugates. The peptide nucleic acids (PNA)/DNA and peptides may be appended either by azide or alkyne groups. The cycloaddition reaction between the azide and alkyne appended substrates allows the synthesis of the desired conjugates in high purity and yields irrespective of the sequence and functional groups on either of the two substrates. The versatile approach could also be employed to generate the conjugates of peptides with thioacetamido nucleic acid (TANA) analog. The click reaction is catalyzed by Cu (I) in either water or in organic medium. In water, similar to 3-fold excess of the peptide-alkyne/azide drives the reaction to completion in 2 h with no side products.